Prevalence of port site infection after laparoscopic cholecystectomy in a tertiary care center: a retrospective descriptive study - Maharjan, Shanta Bir; Guragain, Nikol; Yogi, Bhirkuti; Sapkota, Hari Prasad (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Laparoscopic cholecystectomy is the gold standard surgical procedure for gallstone diseases. Despite many benefits, laparoscopic cholecystectomy has certain complications including port site infections. This study aims to determine the prevalence of port site infections in patients undergoing laparoscopic cholecystectomy for gallstone diseases and to find the difference in prevalence of port site infection due to intraoperative spillage or use of endobag. Method: This study was a retrospective, descriptive cross-sectional study conducted in Unit II of the Department of Surgery, Patan Academy of Health Sciences from June 2022 to May 2025. The study was conducted after the approval of the Institutional Review Committee (Ref. drs2511112150). We retrospectively collected the data of the patients who satisfied the inclusion and exclusion criteria. Result: This study enrolled 107 patients who had undergone laparoscopic cholecystectomy. The mean age was 44.85±11.89 years. Our study noted the spillage of bile, pus or stone in 30(28.03%) patients but the use of endobag in only 18(16.82%) patients. Port site infection was recorded in 28(26.16%) patients, where all infected ports were umbilical and superficial. Port site infection was noted in three (16.66%) patients with use of endobag and 25(28.09%) patients in whom the endobag was not used. Among the patients with spillage, port site infection was noted in nine (30.00%) patients and among patients without spillage, it was noted in 19(24.68%) patients. Conclusion: Port site infection was high (26.16%) in this study. Institutional-level clinical audits and quality improvement projects are recommended.